Analisis Ekonomi Usaha Peternakan Ayam Pedaging Pola Kemitraan Inti-Plasma di Kabupaten Lamongan - Elly Ismiyah (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2020)
Lamongan Regency is the district with the highest broiler population in East Java in 2017-2018. The business opportunity in the field of broiler breeding is a business that is considered promising, maintenance cycles that only take about 35 days make farmers do not have to wait a long time to enjoy the results, especially since they have developed livestock with a core-plasma pattern. With a mutualism relationship where many breeders have limited capital, while partner companies also need a place to raise broilers that are not only focused on one area, a pattern of core-plasma partnerships has developed between the company and breeders. This study analyzes the economic side of animal husbandry business with a core-plasma partnership pattern with PT. CA, Lamongan Unit as a case study. Breeder-01 with a concrete cage and other wood and bamboo materials, has an investment of Rp. 450,000,000 (capacity of 14,000 broilers) is estimated to be 30 years old, based on net income in the last cycle of Rp. 25,160,000 and the 3% interest rate yields an NPV of Rp. 2,826,618,448, ROR value of 28.54%, Payback Period of 2.28 years. Whereas Breeder-02 with a wooden cage and other materials made of bamboo, has an investment of Rp. 250,000,000 (12,000 capacity) estimated to be 15 years old, based on net income in the last cycle of Rp. 21,830,000 and an interest rate of 3% resulting in an NPV of Rp. 1,497,984,299, ROR value of 33.47%, Payback Period 1.14 years. The results of the sensitivity analysis can also be concluded that investment in broiler breeding business in nucleus-plasma partnership pattern is feasible.